Review of the genus Diaphanogryllacris (Orthoptera: Gryllacrididae: Gryllacridinae) with description two new species from China - Du, Bao-Jie; Bian, Xun; Shi, Fu-Ming (Zootaxa, 2016)
Two new species of the genus Diaphanogryllacris from China are described, i.e. Diaphanogryllacris brevispina sp. nov. and Diaphanogryllacris incavatis sp. nov.. In addition, a distribution map of the species of the genus Diaphanogryllacris from China is presented. All material examined is deposited in the Museum of Hebei University.